2016
DOI: 10.1590/s1679-875920160933064sp2
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian sandy beaches: characteristics, ecosystem services, impacts, knowledge and priorities

Abstract: Sandy beaches constitute a key ecosystem and provide socioeconomic goods and services, thereby playing an important role in the maintenance of human populations and in biodiversity conservation. Despite the ecological and social importance of these ecosytems, Brazilian sandy beaches are significantly impacted by human interference, chemical and organic pollution and tourism, as well as global climate change. These factors drive the need to better understand the environmental change and its consequences for bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(46 citation statements)
references
References 49 publications
0
39
0
7
Order By: Relevance
“…Shallow marine habitats and the surf zone of sandy beaches have long been considered as nurseries for several fish species, many of commercial interest (Monteiro-Neto and Musick 2003, Pereira et al 2015). The high food availability (Amaral et al 2016) and protection from larger fish predators (Félix et al 2007) during the growing phase represent important assets for young fish. Thus, shallow marine habitats play the connectivity role between the young and the adult population (Beck et al 2001) of species that are commonly found in other habitats as adults.…”
Section: Discussionmentioning
confidence: 99%
“…Shallow marine habitats and the surf zone of sandy beaches have long been considered as nurseries for several fish species, many of commercial interest (Monteiro-Neto and Musick 2003, Pereira et al 2015). The high food availability (Amaral et al 2016) and protection from larger fish predators (Félix et al 2007) during the growing phase represent important assets for young fish. Thus, shallow marine habitats play the connectivity role between the young and the adult population (Beck et al 2001) of species that are commonly found in other habitats as adults.…”
Section: Discussionmentioning
confidence: 99%
“…Estes ambientes são responsáveis pela provisão de diversos serviços ecossistêmicos com grande importância social e econômica (alimento, proteção da linha de costa, turismo, lazer etc.) (Carrilho & Sinisgalli, 2018;Amaral et al, 2016) e vêm sofrendo o impacto das mudanças climáticas, do crescimento populacional e da ocupação desordenada (MMA, 2014;Santos & Turra, 2017;Teixeira, 2013 A Região Metropolitana da Baixada Santista (RMBS) foi criada em 1996 e é integrada por nove municípios: Bertioga, Cubatão, Guarujá, Itanhaém, Mongaguá, Peruíbe, Praia Grande, Santos e São Vicente.…”
Section: O Litoral Da Macrometrópole -A Expansão Urbana E Os Fluxos Munclassified
“…Sendo o ambiente costeiro dominante na maioria das regiões tropicais e temperadas (Defeo & McLachlan, 2005), as praias arenosas são um dos ambientes marinhos mais acessíveis ao homem e locais muito populares, consequentemente, é o ambiente costeiro mais utilizado pela população humana (Klein et al, 2004) causando mudanças antropogênicas que podem ter efeitos significativos na estrutura e no funcionamento das comunidades de uma praia (Amaral et al, 2016).…”
Section: Introductionunclassified